2022
DOI: 10.1590/0034-7167-2021-0065
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection in patients with chronic kidney disease under conservative treatment

Abstract: Objectives: to assess the prevalence and associated risk factors for urinary tract infection in patients with chronic kidney disease under conservative treatment and identify the microorganisms isolated in the urine of these patients and the staging of chronic kidney disease. Methods: a cross-sectional, analytical study carried out at the Conservative Treatment Outpatient Clinic of a university hospital in the city of São Paulo. Results: the prevalence of urinary tract infection is 22%. The risk factors Diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Chronic kidney disease (CKD) is one of the most common chronic diseases with the worldwide prevalence estimated to be approximately 13.4% and projected to continue to rise annually, especially in developing countries where renal healthcare is limited [1,2,3]. CKD is emerging in the 21st century as a global public health issue, affecting more than 750 million people worldwide [4]. The prevalence of CKD is increasing worldwide, and the mortality rate continues to be unacceptably high [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chronic kidney disease (CKD) is one of the most common chronic diseases with the worldwide prevalence estimated to be approximately 13.4% and projected to continue to rise annually, especially in developing countries where renal healthcare is limited [1,2,3]. CKD is emerging in the 21st century as a global public health issue, affecting more than 750 million people worldwide [4]. The prevalence of CKD is increasing worldwide, and the mortality rate continues to be unacceptably high [5].…”
Section: Discussionmentioning
confidence: 99%
“…The factors, together with increasing diabetes prevalence and an aging population, will result in significant global increases in chronic kidney diseases (CKD) end stage renal disease (ESRD) patients. Graciano Coutinho et al, [4] on their study on urinary tract infection in patients of chronic kidney diseases in São Paulo, Barazil reported that the risk factor Diabetes Mellites, hypertension, heart disease, neoplasms and thyroid and A urinary tract infection (UTI) is a bacterial infection that affects part of the urinary tract. When it affects the lower urinary tract, it is known as a simple cystitis (a bladder infection) and when it affects the upper urinary tract it is known as pyelonephritis (a kidney infection).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary tract infections occupy a special niche among diseases of infectious etiology, since many clinical cases, up to 80%, become chronic [ 12 , 13 , 14 ]. This is due to a number of factors: anatomical features (the proximity of anatomical openings, which promotes the migration of opportunistic microorganisms from the intestine), histological factors (features of the transitional epithelium of the urethra and bladder—the ability to form intercellular spaces during the inflammatory process—where microorganisms easily multiply), and characteristics of the pathogens themselves, for example, their adhesion abilities and subsequent biofilm formation [ 12 , 13 , 14 ]. The ability of pathogenic and non-pathogenic microorganisms to form biofilms is one of the leading problems in the field of therapy and prevention of infectious diseases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%